Outcomes of Long-arm Casting Versus Double–Sugar-Tong Splinting of Acute Pediatric Distal Forearm Fractures. Issue 1 (January 2015) - Levy, Jeffrey; Ernat, Justin; Song, Daniel; Cook, Jay B.; Judd, Daniel; Shaha, Steven
Abstract : Introduction: The traditional treatment after closed reduction of distal radius (DR) and distal both bone (DBB) forearm fractures has been application of a long-arm cast (LAC) or a short-arm cast (SAC). Splinting is another option that avoids the potential complications associated with casting. The purpose of this study is to evaluate the maintenance of reduction of DR or DBB fractures placed in a double–sugar-tong splint (DSTS) compared with a LAC in a pediatric population. Methods: This is an IRB-approved, prospective, randomized trial. Patients aged 4 to 12 years with DR or DBB fractures treated at a single institution between 2010 and 2012 were enrolled. After reduction, fractures were placed into either a LAC or a DSTS. Radiographs were reviewed at initial injury, postreduction, and at set intervals for angulation, displacement, and apposition, as well as cast index and 3-point index. The DSTS was overwrapped into a cast after week 1. The immobilization device was changed to a SAC at week 4 or 6. Total duration of immobilization was 6 to 8 weeks. Results: Seventy-one patients were enrolled with 37 in the LAC and 34 in the DSTS. Average age was 8.73 years (range, 4 to 12) with 43 being males. There were 28 isolated DR and 43 DBB fractures. There were no week-to-week differences between the 2 groups in regards to sagittal alignment, coronal alignment, apposition, or displacement. Sagittal alignment at immediate postreduction and week 2 showed that the DSTS was slightly better (average 2.0 vs. 5.0 degrees, respectively, P =0.04). For the entire treatment period there was an increased risk of loss of reduction of ≥10 degrees in the LAC group versus the DSTS group (7 patients vs. 2 patients, respectively, P =0.0001), and of meeting the criteria for remanipulation (10 patients vs. 5 patients, respectively, P =0.01). At cast removal, there was no difference between groups. Conclusions: Although there were significant differences between the 2 groups with regards to risk of reduction loss, the DSTS and LAC were comparable in maintenance of reduction at the time of cast removal. Both the DSTS and LAC are appropriate immobilization devices for these pediatric fractures. Level of Evidence: Level II—prospective, comparative study.